Adding an "E" to Free - Ekart, Donna F. (My University, 2011)
In a perfect world, you’d have the funds to buy or subscribe to all the ebooks and ejournals your users want. You’d have a couple dozen Kindles and iPods, loaded with content, on hand to loan out. You’d have a magical library Netflix account that would let all your patrons watch movies from home by entering their library card numbers; ditto for iTunes that would stream music from your collection. Someday, maybe. But for today, it’s possible to build a decent e-collection around free resources. Here are several of my favorite free e-resources for you to check out.